Evaluation of surface water quality using water quality indices (WQIs) in Lake Sukhna, Chandigarh, India - Maansi (SpringerOpen, 2021)
Abstract To assess the surface water quality of Sukhna Lake, 13 physico-chemical parameters like temperature, pH, transparency, dissolved oxygen, electrical conductivity, total dissolved salts, chloride, total Aalkalinity, total hardness, calcium, magnesium, nitrate and phosphate were investigated on monthly basis for a period of two year (July 2016–June 2018) by using standard procedures. The results were compared with the values or ranges mentioned by standard organizations (WHO and BIS) for assessing the water quality and these revealed that the lake water was turbid and under DO distress. Various water quality indices like water quality index (WQI), Canadian Council Ministry of Environment (CCME)-WQI and comprehensive pollution index (CPI) were used to assess the water quality status in the Sukhna Lake. The range of WQI (59.74–83.49) indicated that the water quality status of the lake belonged to good category while those of CCME-WQI (52.4–81.61) revealed that water quality fallen from marginal to good category and those of CPI (0.4–0.7) indicated fair state of water in the lake. Overall the water quality in Sukhna Lake has been found deteriorated during second year in comparison the first year during the study time.